Investigation of Flexural Properties and Thermal Conductivity for Wood Dust Filled Epoxy. - Al-Shabander, Ban M (Al-Nahrain Journal of Science, 2013)
This paper presents the flexural properties and thermal conductivity of composites made from wood dust filler particles and epoxy resin. The flexural tests of composites, based on wood dust filler particles at different filler contents viz. (0, 1, 3, 5, 7 and 10) Wt%, were carried out using an Instron universal testing machine according to ASTM D790 and their results were presented. Experimental results showed that the flexural strength of the composites decreased with the increase of the filler particle content. Concerning the relation between the Young’s modulus and percentage of filler for flexural tests, it was found to be directly proportional at low concentrations of wood dust, at concentrations of 7 Wt% and 10 Wt% wood dust, the Young’s modules decreases with increasing wood dust, with values of (1.870) and (1.824) GPa respectively.Thermal tests were done using Lee’s disk to determine the coefficient of thermal conductivity. The results obtained showed that the increasing weight percentage of wood dust in the composite leads to decreasing the thermal conductivity.